Conflicting Effects of Context in Change Detection and Visual Search: A Dual Process Account. - LaPointe, Mitchell R. P.; Milliken, Bruce (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2017)
Congruent contexts often facilitate performance in visual search and categorisation tasks using natural scenes. A congruent context is thought to contain predictive information about the types of objects likely to be encountered, as well as their location. However, in change detection tasks, changes embedded in congruent contexts often produce impaired performance relative to incongruent contexts. Using a stimulus set controlled for object perceptual salience, we compare performance across change detection and visual search tasks, as well as a hybrid of these 2 tasks. The results support a dual process account with opposing influences of context congruency on change detection and object identification processes, which contribute differentially to performance in visual search and change detection tasks.